Pertambahan Bobot Badan dan Waktu Pembusukan Daging Ayam Broiler yang Diberi Ekstrak Jaloh Dikombinasi dengan Kromium - Sugito Sugito; Erdiansyah Rahmi; Azhari Azhari; M. Isa (Jurnal Agripet, 2010)
The gain body weight and Spoilage of meat broiler which giving jaloh extract to combine with chromiumABSTRACT. A study was conducted on broiler chickens under heat stress to evaluate the effect of combined jaloh (Salix tetrasperma Roxb) extract with chromium mineral in the body weight, value of feed ratio conversion, and time to meat to become decomposed. Twenty four of 20-day old Cobb female broiler chickens were randomly assigned and divided to 4 treatment groups. Completely randomized design was used in this study. The treatments were as follows: 1) chickens given no heat stress and jaloh extract nor chromium (tCp); 2) chickens under heat stress without given jaloh extract nor chromium (Cp); 3) chickens under heat stress and given jaloh extract in 1.000 mg/lt drinking water (Cp+Ej); and 4) chickens under heat stress, given jaloh extract in 1.000 mg/lt drinking water, and chromium in 1.000 ug/lt drinking water (Cp+Ej+Cr). Heat stress given was 33 1oC of cage temperature during 4 hours per day within 15 days. Jaloh extract and chromium treatments in drinking water were given at 2 hour before cage temperature reaching 33 1oC and were stopped being given after 1 hour, when cage temperature back to room temperature. On the 16th day of the study chickens were measured before slaughtered. Samples obtained were chicken meat that taken from breast part (musculus pectoralis). The result suggested that either giving jaloh extract per se at the dose of 1.000 mg/lt in drinking water or combine it with chromium that given two hours before cage temperature reaching 33 1oC, can prevent chickens from decreasing their body weight, decreasing value of feed ratio convertion, and extending time to meat to become decomposed.